Social presence effect in language comprehension: evidence from event-related potential (ERP) research - Teng Yu; Xue Sui; Yu tong Li (PeerJ)
Objective This study aimed to examine the impact of social presence on Chinese reading comprehension and associated neural responses. Methods Participants tasked with reading Chinese sentences either alone or in the presence of others and subsequently assessing the accuracy of the sentences’ meanings. Concurrently, we recorded the participants’ electrical brain responses to critical word processing. Results Behavioral results indicated no significant effect of social presence on the judgment of sentence accuracy. Electroencephalogram (EEG) results, however, revealed that reading in the presence of others elicited more pronounced left anterior negativity (LAN) components in the left front of the scalp compared to reading alone. Additionally, incorrect meanings triggered larger N400 and P600 amplitudes in the mid-parietal region than correct meanings. Conclusion Social presence intensifies early neural responses during the reading of Chinese sentences, although it does not influence semantic integration or conflict resolution. These findings support the notion that social context affects language processing.